PERBAIKAN ASPEK MANAJEMEN PRODUKSI SERTA PELUASAN PASAR SASARAN ANTAR PULAU DAN EKSPOR BAGI PRODUK KERAJIAN SABLON KULIT DI DESA KAYEN SUKOHARJO - Suwardi - Suwardi; Iwan - Hermawan (Politeknik Negeri Semarang, 2015)
Sukoharjo local economy continues to grow,with an increase in revenue of IDR 20 Billion,which is supported by 16.541 medium andsmall industries (BPS; 2010), in the sameamount of volume of exports amounted to 196,680,879.38 for the District. Map ofIndustry and SMEs spread on an area of 46.6thousand km2 which consists of 12 Districts,150 villages and 17 urban villages. Based onapproach to growing attractiveness of theindustry related to the creative industries inCentral Java icon possess many industriessupported by the District Sukhorajo, such asfurniture industry of waste paper (IwanHermawan, 2009), Rattan Furniture Industryand Handicraft Banana, Leather CraftIndustry from Pari Fish, Water HyacinthFurniture Industry, Handicraft carvingdecoration, craft industry Gamelan. Screenprinting industry Leather is one industry thatis growing and requires special attentionfrom various groups including localgovernment. Constraints on this industry alsocontributed to revenue growth for exportbased,but many obstacles such as productquality,low-level variants and marketexpansion constitute constraints to beresolved if the industry wants Sablon Leatherin Sukoharjo still to exist.